Effectiveness of Adding Home Bleaching Time With 10% Carbamide Peroxide : Literature Review - Mahardiansyah, Ryan; Dyah Harniati, Etny; Aria Sari, Ismaya (Journal Research of Social Science, Economics, and Management, 2022)
Changes in the color of teeth to become darker are a lot of complaints by the public. Bleaching is a whitening treatment for teeth that have changed color. Home bleaching is a bleaching that can be done at home under the supervision of a dentist using 10% carbamide peroxide for a period of more than 2 weeks. The purpose of this study was to determine the effectiveness of 10% carbamide peroxide as a home bleaching agent with an extended period of time against tooth discoloration. This type of research is Literature Review using Google Scholar, Web of Science, and Pubmed using keywords that have been carried out, obtaining 9 articles that match the research criteria. The results showed that 10% carbamide peroxide with an application of more than 2 weeks gave effective and stable results, but the effect was also greater. The use of 10% carbamide peroxide as a home bleaching agent with an additional effective time for discoloration was seen based on a literature review